THE IMPACT OF THE MODEREN WORK SYSTEM ON THE SOCIAL LIFE OF RISTA BAN WORKSHOP WORKERS IN GORONTALO - Yuniarti, Putri; Aisya, Siti Nur; Al-Bakri, Suci Rama; Hikmah, Hikmah; Kiama, Faulina U.; Karim, Titan; Hasan, Alga Pratama; Harold, Rudi (PERSPEKTIF: Journal of Social and Library Science, 2025)
This study aims to analyze the impact of modern work systems on the social, economic, and emotional lives of workers at the Rista Ban Workshop in Gorontalo City. Using a descriptive qualitative approach and case studies, data were collected through in-depth interviews with the workshop owner and three employees with varying lengths of service. The results show that a rational, standardized, and efficiency-oriented work structure provides economic benefits for workers through basic salaries, meal facilities, and additional income from overtime. However, this system also gives rise to complex social dynamics, such as imbalances in work contributions, potential conflicts between workers, and increased psychological burdens on senior workers. These conditions align with Max Weber's concept of the "iron cage," in which workers are bound by a rational work system that limits flexibility and personal freedom. These findings confirm that modern work systems in small, informal sector businesses have a dualistic impact: strengthening workers' economic stability while simultaneously creating social and emotional stress that requires attention in workforce management.